Analysis of Infiltration Rate in Community Forest Land (HKm) Wombo Rengge Kala, Dompu District, West Nusa Tenggara - Nurwahdania, Nurwahdania; Ichsan, Andi Chairil; Wulandari, Febriana Tri (Jurnal Biologi Tropis, 2025)
The amount of water that enters the soil per unit of time is known as the infiltration rate, whereas infiltration itself is the process by which water flows into the soil, typically via rainfall. The purpose of this study was to determine the infiltration rate and the impact of infiltration and to formulate community efforts to control infiltration in the Ampang Riwo community forest. Determination of the research sampling point using purposive sampling. This study used 4 infiltration rate test points and 4 samples were taken for soil samples, namely Vegetation is not dense, very steep land (V1L1), Vegetation is not dense, rather steep land (V1L2), Vegetation is dense, very steep land (V2L1), and Vegetation is dense, rather steep land (V2L2). Measurements were taken using a double ring infiltrometer. The results of the study showed that there were 3 plots that had a fairly fast classification but had different infiltration rate values. The first plot V1L1 which had an infiltration rate value of 150 cm/hour, the second plot V2L1 had an infiltration rate value of 108 cm/hour, In the third plot V2L2 had an infiltration rate value of 186 cm/hour, in the plot V1L2 had a fast infiltration classification, an infiltration rate value of 204 cm/hour. This study there were 12 respondents, namely farmers who had cultivated land. The characteristics of the respondents included age and education level. Based on the results of the study, the perception of cultivators regarding the infiltration rate was obtained with a total of 13 respondents for 10 questions, on average answering strongly agree and agree. For strongly agree 30.77% and 69.23% agreed.